Branched‐chain amino acids reduce hepatic iron accumulation and oxidative stress in hepatitis C virus polyprotein‐expressing mice. (18th September 2014) - Korenaga, Masaaki; Nishina, Sohji; Korenaga, Keiko; Tomiyama, Yasuyuki; Yoshioka, Naoko; Hara, Yuichi; Sasaki, Yusuke; Shimonaka, Yasushi; Hino, Keisuke
Abstract Background & Aims Branched‐chain amino acids (BCAA) reduce the incidence of hepatocellular carcinoma (HCC) in patients with cirrhosis. However, the mechanisms that underlie these effects remain unknown. Previously, we reported that oxidative stress in male transgenic mice that expressed hepatitis C virus polyprotein (HCVTgM) caused hepatic iron accumulation by reducing hepcidin transcription, thereby leading to HCC development. This study investigated whether long‐term treatment with BCAA reduced hepatic iron accumulation and oxidative stress in iron‐overloaded HCVTgM and in patients with HCV‐related advanced fibrosis. Methods Male HCVTgM were fed an excess‐iron diet that comprised either casein or 3.0% BCAA, or a control diet, for 6 months. Results For HCVTgM, BCAA supplementation increased the serum hepcidin‐25 levels and antioxidant status [ratio of biological antioxidant potential (BAP) relative to derivatives of reactive oxygen metabolites (dROM)], decreased the hepatic iron contents, attenuated reactive oxygen species generation, and restored mitochondrial superoxide dismutase expression and mitochondrial complex I activity in the liver compared with mice fed the control diet. After 48 weeks of BCAA supplementation in patients with HCV‐related advanced fibrosis, BAP/dROM and serum hepcidin‐25 increased and serum ferritin decreased compared with the pretreatment levels. Conclusions BCAA supplementation reduced oxidative stress by restoring mitochondrial function and improved iron metabolism by increasing hepcidin‐25 in both iron‐overloaded HCVTgM and patients with HCV‐related advanced fibrosis. These activities of BCAA may partially account for their inhibitory effects on HCC development in cirrhosis patients.